2020
DOI: 10.3390/microorganisms9010077
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Cathodic Biofilm Growth Capabilities of Kyrpidia spormannii EA-1 by Undirected Mutagenesis

Abstract: The biotechnological usage of carbon dioxide has become a relevant aim for future processes. Microbial electrosynthesis is a rather new technique to energize biological CO2 fixation with the advantage to establish a continuous process based on a cathodic biofilm that is supplied with renewable electrical energy as electron and energy source. In this study, the recently characterized cathodic biofilm forming microorganism Kyrpidia spormannii strain EA-1 was used in an adaptive laboratory evolution experiment to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Previously it was shown that at the initially uncovered cathode a part of the dissolved oxygen might be abiotically reduced into reactive oxygen species (ROS) (Hackbarth et al, 2020; Jung et al, 2020). As the initial cell number decreases, the cumulative ROS-detoxification capacity of the cells also decreases, possibly preventing a sufficient initial cathode coverage that serves as an insulator to minimize abiotic ROS formation.…”
Section: Resultsmentioning
confidence: 99%
“…Previously it was shown that at the initially uncovered cathode a part of the dissolved oxygen might be abiotically reduced into reactive oxygen species (ROS) (Hackbarth et al, 2020; Jung et al, 2020). As the initial cell number decreases, the cumulative ROS-detoxification capacity of the cells also decreases, possibly preventing a sufficient initial cathode coverage that serves as an insulator to minimize abiotic ROS formation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the utilization of this technique is not only limited to anodic processes but can also improve cathodic processes used for bioelectrosynthesis as well as biofilm-based gas fermentation. Consequently, following experiments will aim for the development of spray biofilms containing methanogens, acetogens or knallgas bacteria as biocatalysts and their application on cathodes in bioelectrochemical systems [ [36] , [37] , [38] ].…”
Section: Discussionmentioning
confidence: 99%
“…As the most likely mechanism might be the consumption of hydrogen which is produced even at rather high potentials at pH 3, selective evolution experiments also suggested that the ability of the organism to grow also with molecular sulfur as electron donor might have an impact. Jung and colleagues grew the organism for several transfers on cathodes and observed a fourfold increase of the biofilm accumulation rate (Jung et al 2021 ). Bioinformatic analysis revealed that the adapted cells carried three loud mutations compared to the progenitor strain.…”
Section: Extremophilic Organisms Thriving On Cathodesmentioning
confidence: 99%
“…Still, as a genetic system is not available for the organism thus far, direct proof for a potential influence of the electron transport chain from sulfur in electron import from cathodes is still missing. Nevertheless, that the production of reactive oxygen species on the electrodes also hampers the activity of K. spormannii is rather undoubtedly expressed by the mutation within the perR regulator gene which will likely lead to constitutive production of proteins dealing with oxidative stress (Jung et al 2021 ). Moreover, Pillot et al recently modified graphite cathodes by means of electrodeposition with different catalytically active metals such as platinum that enhance abiotic hydrogen evolution.…”
Section: Extremophilic Organisms Thriving On Cathodesmentioning
confidence: 99%